X-ray Fluorescence Emission Tomography (XFET) with Novel Imaging Geometries – A Monte Carlo Study - Meng, L. J. (2011)
This paper presents a feasibility study for using two new imaging geometries for synchrotron X-ray fluorescence emission tomography (XFET) applications. In the proposed approaches, the object is illuminated with synchrotron X-ray beams of various cross-sectional dimensions. The resultant fluorescence photons are detected by high-resolution imaging-spectrometers coupled to collimation apertures. To verify the performance benefits of the proposed methods over the conventional line-by-line scanning approach, we have used both Monte Carlo simulations and an analytical system performance index to compare several different imaging geometries. This study has demonstrated that the proposed XFET approach could lead to a greatly improved imaging speed, which is critical for making XFET a practical imaging modality for a wide range of applications.